(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the role of Constructivism theory in international relations, the results of the research of scientists who founded this theory, as well as evidence of the importance of Constructivism theory in modern international relations (the end of the Cold War, the European Union, international human rights norms, global governance) and the internal divisions of Constructivism theory - information about classical constructivism, critical constructivism, poststructuralist constructivism, feminist constructivism, and normative constructivism is discussed. While reading the article, the reader will witness the fact that world-renowned scientists (Nicolas Onuf, Alexander Wendt, Emanuel Adler, Kayin Ringmar, Liliana Riga, etc.) have tried to prove the importance of Constructivism theory in the management of the state and society with their research. Especially in the article, the conflict of the theory of Constructivism with the theories of Realism and Liberalism, in addition, the opinions about the absence of a single system in approaches to foreign policy, international relations and internal management are also put forward.